Exploring the Use of Loose Parts Boxes in Developing Creativity and Problem-Solving Skills in Early Childhood: Eksplorasi Pemanfaatan Loose Parts Box dalam Mengembangkan Kreativitas dan Kemampuan Problem Solving Anak Usia Dini - Umamah, Achidiyah Zuke; Halim, Abdul; Nafisah, Aisyah Durrotun (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Early childhood education requires play-based learning that allows children to explore, express ideas, and develop cognitive, social-emotional, and language abilities through meaningful experiences. Specific Background: Loose parts box activities provide open-ended materials that children can move, combine, modify, and reconstruct, while challenge cards offer light scaffolding to guide exploration without limiting freedom. Knowledge Gap: Previous studies have mostly reported outcomes of loose parts use, while the learning processes, problem-solving patterns, resilience, and child interaction during structured open-ended play remain insufficiently explored. Aims: This qualitative case study examined the use of loose parts boxes with challenge cards in developing creativity and problem-solving skills among 13 children aged 5–6 years through participant observation, teacher interviews, and documentation across six meetings. Results: The findings showed progressive improvement in independent material exploration, object combination into new constructions, repeated attempts after failure, verbal expression of original ideas, and independent use of challenge cards. Three problem-solving patterns emerged: trial and error, creative adaptation, and peer collaboration. Challenge cards functioned as scaffolding, while resilience appeared when children changed strategies after failure. Novelty: The study reveals how loose parts boxes combined with challenge cards create a structured yet flexible play environment that supports exploration, adaptation, and collaborative problem solving. Implications: This medium can serve as an inclusive alternative for play-based early childhood learning, although contextual findings require cautious generalization. Highlights • Open-ended materials encouraged independent exploration and new object construction.• Challenge cards provided scaffolding without restricting children’s exploratory freedom.• Trial and error, adaptation, and peer collaboration appeared naturally during activities. Keywords Loose Parts Box; Creativity; Problem Solving; Early Childhood; Scaffolding